Body Image and Eating Habits of Students Female Student at Vokasi Senior High School Sibolga - Desty Adinda; Etti Sudaryati (Pena Cendekia Insani, 2021)
Adolescence is a critical stage in adolescents' development during the first decade of life, and as a result, body image becomes a concern for adolescents, particularly young women. Body image will cause young women to alter their eating habits to achieve the body image they desire. This study is to ascertain female students at vokasi senior high school body image and eating habits. Method: This research was carried out at vokasi senior high school in Sibolga in June 2016 - March 2017. The population of this study were young women of vokasi senior high school in Sibolga, totalling 449 students in 2016, and the sample is 90 students. Data on eating habits were obtained through a 24-hour food recall questionnaire to see the nutritional intake of adolescent girls. Body image data was obtained by direct interview using a questionnaire tool through the Figure Rating Scale (FRS) method. The results of this study indicate that who have bad eating habits (2.2%), based on filling out the food frequency questionnaire, students who have bad eating habits, namely never having breakfast at all, eating frequency only once a day, In addition, the consumption of foods that are not diverse. This study indicates that the negative body image is 43.3%, and the body image in the negative category is 56.7%. This study concludes that there are still many young women who have a body image in the positive category and have good eating habits. Even though the body image is in the negative category, the eating habits are still in the good category.